Authentic leadership for creativity and innovation: The moderating role of motivating language - Yuni Siswanti; Muafi Muafi (SA Journal of Human Resource Management)
Orientation: Creativity and innovation are essential in coping with a complex business environment that becomes more complex and rapidly changing.